Massage contents in the medical career. Its application in the community - García Ruiz, Jorge Enrique; Ramos Vives, Madelaime; Iglesias Iglesias, Modesto Antonio; Montano Baños, Iván Javier (SCT Proceedings in Interdisciplinary Insights and Innovations, 2023)
Massage is one of the easiest means within our reach to achieve good health and maintain it. Taking into account its importance, a research was carried out at the Faculty of Medical Sciences “Dr. Ernesto Che Guevara de la Serna” of Pinar del Río, in the year 2023, with the objective of arguing the importance of implementing massage contents and the design of an optional course for the medical career, deepening in diverse pathologies to be treated in community care. Methods: the general dialectical materialist method was used, making possible the use of theoretical and empirical methods. Likewise, a space is dedicated to the conceptual analysis and its characteristics. Results: the analysis of the application of massages in medical assistance, generalities, classification, physiological effects and influences on the different organs and systems and their application in several pathologies are systematized. Conclusions: the importance of the insertion of massage contents in the elective courses of the medical career is recognized and an elective course was designed with the fundamental theoretical and practical contents on massages applicable in the care of patients in the community, a complementary booklet and slides for its study, which when implemented will contribute to the better training of the physician and his professional performance in community care for a better rehabilitation of patients, responding to the current needs of society.